2009
DOI: 10.1002/jmor.10759
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of skin incubation in Pipa carvalhoi (Anura: Pipidae)

Abstract: South American Pipidae show a unique reproductive mode, in which the fertilized eggs develop in temporarily formed brood chambers of the dorsal skin after eggs have been deposited on the back of the female. We studied the skin incubation of Pipa carvalhoi using light microscopy and scanning electron microscopy. The skin consists of a stratified epithelium with a one-layered stratum corneum, and the dermis. The dermis of the dorsal skin of nonreproductive and reproductive females lacks a distinct stratum compac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…This modification might be important to make the dermis more malleable and able to better accommodate the eggs and the future embryos. Such characteristic was also noted by Greven and Richter (2009) and, according to them, is present in females of all Pipa species. Through polarized microscopy after picrosirius staining, two types of dermal collagen fibers were distinguished, one more related to the dense regions (Type I collagen, which is thicker and appears in red), and another related to looser regions (Type III collagen, which is thinner and more delicate, appearing in green) (Junqueira et al, 1979).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This modification might be important to make the dermis more malleable and able to better accommodate the eggs and the future embryos. Such characteristic was also noted by Greven and Richter (2009) and, according to them, is present in females of all Pipa species. Through polarized microscopy after picrosirius staining, two types of dermal collagen fibers were distinguished, one more related to the dense regions (Type I collagen, which is thicker and appears in red), and another related to looser regions (Type III collagen, which is thinner and more delicate, appearing in green) (Junqueira et al, 1979).…”
Section: Discussionmentioning
confidence: 83%
“…We have shown that increase in vascularization is more evident from the 14 th day, when the embryos are in the later developmental stages and no yolk is available inside the egg, although it was seen inside the embryos intestines. This evidence and the close contact between capillaries through a very thin epithelium lead us to suppose that there is some type of interaction between maternal and embryonic tissues in P. carvalhoi (Fernandes, 2007;Fernandes et al, 2007), an observation also made by Greven and Richter (2009). Gas exchange was suggested for the marsupial frog Gastrotheca (Del Pino, 1980).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Fernandes et al (2011) argued in favor of some type of interaction between embryonic and maternal tissues in P. carvalhoi. This suggestion was based on the presence of a large number of blood capillaries in the skin of the embryo, and a thin epidermis lacking a stratum corneum and a heavily vascularized dermis forming the walls of the brood chambers (Greven andRichter 2009, Fernandes et al 2011). A vascularized tail may also suggest a role in gas exchange.…”
Section: Pipa Arrabali Staging Table 1883mentioning
confidence: 99%